TINJAUAN KETERDAPATAN BATUAN ULTRAMAFIK DALAM KOMPLEK OFIOLIT CILETUH DI DAERAH CILETUH, JAWA BARAT - Hutabarat, Johanes; -, Ismawan (Bulletin of Scientific Contribution, 2015)
Ultramafic rock is defined as rock with a color index of more than 70, and most have good characteristics as igneous plutonic and metamorphic rocks. Ultramafic rocks in the area Ciletuh revealed in outcrops scattered as "pockets" (enclaves) in Ciletuh formation, with the tendency of azimuth northeast trending ± southwest, which gives the impression of intrusion body, or as blocks of exotic in Ciletuh Formation. Rock composed of peridotite and serpentinite of massive to foliated; associated with gabbro, basalt pillow structure. Association of peridotite-serpentinite with gabbro, basalt structure of the pillow, giving the impression that the rock may represent parts of the set ophiolite. Based on occurences in the field, where the body is suspected origin of ultramafic rocks in the ophiolite complex Ciletuh speculated a continuous sheet relicts oceanic crust that is emplaced above microcontinent. Part sheet becomes incomplete (dismembered) during emplacement, and then buried (burial) by next geological events (possible sedimentation process produces Formation Ciletuh) that largely hides covered by ofiolitic, and leaving only the ultramafic body which spread in most Ciletuh areas at West Java.